1996
DOI: 10.1021/jp960729n
|View full text |Cite
|
Sign up to set email alerts
|

Intrazeolite Photochemistry. 12. Ship-in-a-Bottle Synthesis and Control of the Photophysical Properties of 9-(4-Methoxyphenyl)xanthenium Ion Imprisoned into Large-Pore Zeolites

Abstract: The 9-(4-methoxyphenyl)xanthylium ion (AnX + ), a bulky cation that according to molecular modeling simulations cannot enter through the 7.4 Å pore opening of tridirectional large-pore zeolites Y and β, has been prepared by ship-in-a-bottle synthesis within the supercages of these two zeolites. The synthetic procedure involves two steps: (i) generation of xanthylium cation (X + ) adsorbed within the zeolite by treatment of xanthydrol onto the H + form of these solids; (ii) electrophilic attack of the cation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…9‐(4‐Methoxyphenyl)xanthylium has also been prepared by a ship‐in‐a‐bottle synthesis inside the cavities of zeolites Y and Beta by electrophilic attack of preformed xanthylium cation180 on electron‐rich anisole (Scheme ) 181. The resulting 9‐arylxanthylium remains entrapped inside the zeolite supercages, molecular modelling indicating that the conformational rotation of the anisyl substituent over the xanthylium cores is impeded by the encapsulation (Figure 7).…”
Section: B Applications Of Zeolite‐embedded Guest Systems Obtained Bmentioning
confidence: 99%
See 1 more Smart Citation
“…9‐(4‐Methoxyphenyl)xanthylium has also been prepared by a ship‐in‐a‐bottle synthesis inside the cavities of zeolites Y and Beta by electrophilic attack of preformed xanthylium cation180 on electron‐rich anisole (Scheme ) 181. The resulting 9‐arylxanthylium remains entrapped inside the zeolite supercages, molecular modelling indicating that the conformational rotation of the anisyl substituent over the xanthylium cores is impeded by the encapsulation (Figure 7).…”
Section: B Applications Of Zeolite‐embedded Guest Systems Obtained Bmentioning
confidence: 99%
“… Molecular model of the 9‐(4‐methoxyphenyl)xanthylium cation encapsulated within an all ‐ silica zeolite Y supercage (taken from ref 181…”
Section: B Applications Of Zeolite‐embedded Guest Systems Obtained Bmentioning
confidence: 99%
“…Once formed, the synthesized molecules are permanently entrapped within the zeolite supercage and can neither escape nor diffuse between cavities. This strategy was initially applied to the preparation of metallic complexes [47,48] but has been expanded in recent years to the synthesis of encapsulated metallophthalocyanines [49] and organic ions and molecules [50][51][52][53]. This topic has also been recently reviewed [12,34].…”
Section: Ship-in-a-bottle Synthesismentioning
confidence: 99%
“…It has also been demonstrated that a number of organic cations, having a submillisecond lifetime in solution, become indefinitely persistent when incorporated inside the rigid framework of a zeolite [50][51][52]140]. In one example, the encapsulated dibenzotropylium cation was observed to persist within the zeolite nanochannel for longer than 10 years.…”
Section: Stabilization Of Reactive Intermediatesmentioning
confidence: 99%
“…In comparison with homogeneous solution, the channels, cages, and cavities within these porous materials exhibit microheterogeneity in polarity, acidity and electric field and restricted mobility, and this has been frequently invoked to explain the novel photochemistry and photophysics observed. Many investigations have been made into the photophysical properties of incorporated guests such as neutral molecules (4,5), organic cations (6–9) and more recently inorganic photosemicon‐ductors such as titanium dioxide (TiO 2 ) (10,11). Depending on the zeolite type and the nature of the guest, several intriguing phenomena have been observed including delayed fluorescence, room temperature phosphorescence and novel decay kinetics i.e.…”
Section: Introductionmentioning
confidence: 99%